Evolutionary Leap in Endodontics. Case report - Camargo , Jose Maurício Paradella de (2021)
The Leap protocol combines the newest and most active association of reciprocal-rotary instrumentation, aluminum insert ultrasonic, and diode laser. The reciprocal-rotary technique consists of Niti instruments used in different motions depending on the stage of the treatment and promotes the balanced cutting effectiveness and reduced risk of fracture files. Moreover, it creates a centered and tapered shape. The aluminum tip for the ultrasonic unit delivers agitation, emulsification, and cavitation of antiseptic solutions that improve the cleaning. The dye and laser use cause the ablation and final disinfection. This paper describes the case of a patient with asymptomatic apical periodontitis in an upper first right molar submitted to endodontic treatment performed with Leap protocol. After conventional procedures, the root canals were prepared by using reciprocal-rotary instrumentation techniques. Between each file a new solution was placed and activated with the ultrasonic handpiece. At the end of instrumentation, the root canals were aspirated, dried with paper points, the indocyanine dye was placed into the root canals and, DaVinci laser was used for 30 seconds. The gutta-percha cones matching the final Niti file were used coated with AH Plus sealer. A periapical radiograph was taken to verify obturation and its anatomical complexity. Six months after the procedure, the patient was asymptomatic, and the radiographic examination showed healthy periradicular tissues. It is concluded that the use of Leap protocol in conventional endodontic treatment was effective, suggesting that this therapy may provide additional benefits to patients when compared to the conventional technique.